Oxaloacetate Protects Rat Liver From Experimental Warm Ischemia/Reperfusion Injury by Improving Cellular Energy Metabolism. Issue 4 (1st March 2019) - Merlen, Grégory; Raymond, Valérie‐Ann; Cassim, Shamir; Lapierre, Pascal; Bilodeau, Marc
Abstract: Liver ischemia/reperfusion injury (IRI) is an important cause of liver damage especially early after liver transplantation, following liver resection, and in other clinical situations. Using rat experimental models, we identified oxaloacetate (OAA) as a key metabolite able to protect hepatocytes from hypoxia and IRI. In vitro screening of metabolic intermediates beneficial for hepatocyte survival under hypoxia was performed by measures of cell death and injury. In vivo, the effect of OAA was evaluated using the left portal vein ligation (LPVL) model of liver ischemia and a model of warm IRI. Liver injury was evaluated in vivo by serum transaminase levels, liver histology, and liver weight (edema). Levels and activity of caspase 3 were also measured. In vitro, the addition of OAA to hepatocytes kept in a hypoxic environment significantly improved cell viability ( P < 0.01), decreased cell injury ( P < 0.01), and improved energy metabolism ( P < 0.01). Administration of OAA significantly reduced the extent of liver injury in the LPVL model with lower levels of alanine aminotransferase (ALT; P < 0.01), aspartate aminotransferase (AST; P < 0.01), and reduced liver necrosis ( P < 0.05). When tested in a warm IRI model, OAA significantly decreased ALT ( P < 0.001) and AST levels ( P < 0.001), prevented liver edema ( P < 0.001), significantly decreased caspase 3 expression ( P < 0.01), as well as histological signs of cellular vesiculation and vacuolation ( P < 0.05). This was associated with higher adenosine triphosphate ( P < 0.05) and energy charge levels ( P < 0.01). In conclusion, OAA can significantly improve survival of ischemic hepatocytes. The hepatoprotective effect of OAA was associated with increased levels of liver bioenergetics both in vitro and in vivo. These results suggest that it is possible to support mitochondrial activity despite the presence of ischemia and that OAA can effectively reduce ischemia‐induced injury in the liver.